EFFECTIVENESS OF WEB-BASED PROGRESSIVE MUSCLE RELAXATION (PMR) ON SLEEP QUALITY IN PATIENTS BREAST CANCER UNDERGOING CHEMOTHERAPY - Amelia, Weny; Sari, Dian Febrida; Syahid, Armein; Espasari, . (Universitas Udayana, 2024)
Breast cancer is the uncontrolled growth of cells or tissue in the breast. Chemotherapy is the first therapeutic choice for treating cancer. One of the symptoms felt by breast cancer patients undergoing chemotherapy is a decrease in sleep quality. Sleep quality is a person's sense of satisfaction with their sleep. Decreased sleep quality can reduce the body's immune system to fight developing cancer cells. The recommended nursing action to overcome sleep disorders in breast cancer patients undergoing chemotherapy is web-based progressive muscle relaxation (PMR). PMR is a technique that focuses attention on muscle activity, by identifying tense muscles and then reducing tension by performing relaxation techniques to get a relaxed feeling. The aim of this study was to determine the effectiveness of web-based PMR on sleep quality in breast cancer patients undergoing chemotherapy at RSUP Dr. M. Djamil Padang. The research design uses a quasi-experiment in the form of a one group pretest-posttest approach. The sampling technique was purposive sampling with a sample size of 25 people. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Statistical test using Paired T-Test. The results showed a significant effect of web-based progressive muscle relaxation (PMR) on sleep quality in breast cancer patients undergoing chemotherapy (p value = 0.000; ? < 0.05). In this study, it can be concluded that there is an influence of web-based progressive muscle relaxation (PMR) on sleep quality in breast cancer patients undergoing chemotherapy at RSUP Dr. M. Djamil Padang. This study recommends web-based progressive muscle relaxation (PMR) as an independent nursing intervention to improve sleep quality in breast cancer patients undergoing chemotherapy. Keywords: Progressive Muscle Relaxation (PMR); breast cancer; chemotherapy; sleep quality